2016
DOI: 10.1097/gox.0000000000001037
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Face Nerve Grafting with Infraorbital Nerve Pathway Protection: Anatomic and Histomorphometric Feasibility Study

Abstract: Smiling is an important aspect of emotional expression and social interaction, leaving facial palsy patients with impaired social functioning and decreased overall quality of life. Although there are several techniques available for facial reanimation, staged facial reanimation using donor nerve branches from the contralateral, functioning facial nerve connected to a cross-face nerve graft (CFNG) is the only technique that can reliably reproduce an emotionally spontaneous smile. Although CFNGs provide spontane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…17 Using SETS transfers of nearby sensory nerves to long nerve grafts can keep the denervated Schwann cells in a growth-supporting state, counteract chronic denervation in long nerve grafts, and improve nerve regeneration and functional outcomes. This concept was clinically applied by Catapano et al, 36 who coapted a contralateral infraorbital nerve branch to the end of a cross-facial nerve graft to improve axonal growth and thus muscle excursion in a facial paralysis cohort of patients.…”
Section: Discussionmentioning
confidence: 99%
“…17 Using SETS transfers of nearby sensory nerves to long nerve grafts can keep the denervated Schwann cells in a growth-supporting state, counteract chronic denervation in long nerve grafts, and improve nerve regeneration and functional outcomes. This concept was clinically applied by Catapano et al, 36 who coapted a contralateral infraorbital nerve branch to the end of a cross-facial nerve graft to improve axonal growth and thus muscle excursion in a facial paralysis cohort of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In line, we performed a detailed surgical dissection of the cutaneous branch of the mylohyoid nerve and quantified its total axon composition, which has not been conducted in the rat. Overall, this data may be helpful in various experimental models for surgical nerve reconstruction models: the supraorbital and infraorbital nerves may be used for corneal neurotization (Catapano et al, 2018 ; Rosenblatt et al, 2020 ) as well as for sensory protection of cross-face nerve grafts for facial reanimation (Placheta et al, 2015b ; Catapano et al, 2016 ) and the mylohyoid nerve has been proposed as a donor nerve for facial nerve reconstruction (Tubbs et al, 2007 ). A better understanding of the neurophysiological processes occurring as a result of the reconstructive procedures may optimize surgical outcomes in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The infraorbital nerve has been studied to a far less significant degree. Catapano et al found that the infraorbital nerve used to contain 975 myelinated fibres in an anatomic and histomorphometric feasibility study [ 81 ]. The authors commented that this number is expected to provide a sufficient number of donor axons to protect the sural nerve graft.…”
Section: Cadaveric Studies Underlying Corneal Neurotizationmentioning
confidence: 99%